Bruno Latour: New Challenges and Inspirations in Political Ecology - Buraj, Ivan (Studia Philosophiae Christianae, 2023)
Political ecology is a recent development in contemporary scholarship. Contrary to popular belief, the French philosopher Bruno Latour was not its originator. Some scholars began to recognise that nature and politics were closely connected back to the time of Montesquieu. Nonetheless, Latour’s political ecology is original in that it features new or revamped concepts that lend it new content and meaning. It includes concepts such as ‘mode of existence,’ ‘actor/network,’ ‘humans’ and ‘non-humans,’ ‘terrestrial’ or ‘Earthbound,’ and offers a new interpretation of the concepts of nature and politics. These concepts are the focus of the first and second parts of the article. The final part looks at their practical application, particularly in connection with Latour’s idea of creating a common world fit for life, or at least survival. ————————– Received: 24/11/2022. Reviewed: 08/03/2023. Accepted: 30/03/2023.